Real‐time continuous monitoring of injection pressure at the needle tip for peripheral nerve blocks: description of a new method. (14th September 2017) - Quadri, C.; Saporito, A.; Capdevila, X.
Summary: The measurement of injection pressure during the performance of peripheral nerve blocks can be pivotal to detect intraneural placement of the needle tip and thus avoid intrafascicular injection. However, injection pressure can only be measured along the injection line (tubing), which is influenced by several factors. The primary aim of this feasibility study was to describe and validate the principle of a novel nerve‐block needle conceived for real‐time continuous monitoring of injection pressures at the needle tip. Our secondary aim was to provide measurements and compare injection pressure values at the needle tip and in the injection line. Four porcine lower limb anatomic models were prepared and extraneural injections were performed with fractioned boluses of 2 ml saline at a controlled infusion rate of 10 ml.min −1 (0.16 ml.s −1 ). Injection pressure at the needle tip was monitored and compared with the pressure in the injection line. The system proved to be reliable. Thirty injections were successfully performed without technical failures. The mean (95%CI) difference between pressures at the needle tip and the injection line varied substantially from 14.33 (12.58–16.08) kPa at 0.5 ml injected volume to 41.56 (39.66–43.45) kPa at the end of the injection. This study demonstrates that the described system allows for real‐time continuous monitoring of injection pressure at the needle tip. Moreover, this study shows that injection pressure values measured in the injection line cannot be assumed to be a reliable indicator of the injection pressure at the needle tip.